Removal of sulfate in a UASB reactor utilizing glucose as substratum at mesophylic temperature - Toncel, Enrique; Gutiérrez, Edixon; Galindo, Andrés; Pérez, Jhonny; Rojano, Roberto; Daza, Sammy (Rev. Téc. Fac. Ing. Univ. Zulia)
Véase archivo PDF